2000
DOI: 10.1037/0022-006x.68.6.1062
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of alcohol use and clinical treatment needs among homosexually active men and women in the U.S. population.

Abstract: Concerns about dysfunctional alcohol use among lesbians and gay men are longstanding. The authors examined alcohol use patterns and treatment utilization among adults interviewed in the 1996 National Household Survey on Drug Abuse. Sexually active respondents were classified into 2 groups: those with at least 1 same-gender sexual partner (n = 194) in the year prior to interview and those with only opposite-gender sexual partners (n = 9,714). The authors compared these 2 groups separately by gender. For men, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
190
4
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(214 citation statements)
references
References 38 publications
15
190
4
5
Order By: Relevance
“…The data on health-linked behaviors are largely consistent with previous literature on consumption of alcohol, nicotine, and drugs in showing greater intakes of all three substances in men than in women, and greater intakes of nicotine and drugs in non-heterosexuals than in heterosexuals (e.g., Ryan, Wortley, Easton, Pederson, & Greenwood, 2001), although we did not find higher alcohol intake in non-heterosexual women compared with heterosexual women, contrary to some studies (Cochran, Keenan, Schober, & Mays, 2000;Drabble, Midanik, & Trocki, 2005). Interestingly, if rate of cognitive decline is associated with such health-linked behaviors, then one might expect homosexual and bisexual members of both genders to show male-typical rates of cognitive decline.…”
Section: Discussionsupporting
confidence: 89%
“…The data on health-linked behaviors are largely consistent with previous literature on consumption of alcohol, nicotine, and drugs in showing greater intakes of all three substances in men than in women, and greater intakes of nicotine and drugs in non-heterosexuals than in heterosexuals (e.g., Ryan, Wortley, Easton, Pederson, & Greenwood, 2001), although we did not find higher alcohol intake in non-heterosexual women compared with heterosexual women, contrary to some studies (Cochran, Keenan, Schober, & Mays, 2000;Drabble, Midanik, & Trocki, 2005). Interestingly, if rate of cognitive decline is associated with such health-linked behaviors, then one might expect homosexual and bisexual members of both genders to show male-typical rates of cognitive decline.…”
Section: Discussionsupporting
confidence: 89%
“…Lesbians and gay men commonly report positive histories of victimization and discrimination (Herek, Gillis, & Cogan, 1999;Hershberger & D'Augelli, 1995;Krieger & Sidney, 1997), particularly in adolescence or young adulthood (D'Augelli, Hershberger, & Pilkington, 1998;Lock & Steiner, 1999). As a consequence, homosexuality may be a risk indicator for higher rates of psychological distress and some mental disorders.Much of the recent population-based research in this area (Bloomfield, 1993;Cochran, Keenan, Schober, & Mays, 2000;Cochran & Mays, 2000a, 2000bFaulkner & Cranston, 1998;Fergusson, Horwood, & Beautrais, 1999;Garofalo, Wolf, Wissow, Woods, & Goodman, 1999;Gilman et al, 2001;Herrell et al, 1999;Lock & Steiner, 1999;Remafedi, French, Story, Resnick, & Blum, 1998;Saewyc, Bearinger, Heinz, Blum, & Resnick, 1998;Sandfort, de Graaf, Bijl, & Schnabel, 2001;Stall & Wiley, 1988) was made possible by the serendipitous inclusion of questions concerning genders of sexual partners in large healthrelated studies of the general population. This attention to the occurrence of homosexual sexual behavior arose out of public health surveillance needs to track risk factors for HIV transmission in the general population.…”
mentioning
confidence: 99%
“…Some, but not all, studies have observed higher rates of major depression (Cochran & Mays, 2000a, 2000bSandfort et al, 2001), suicide attempts (Herrell et al, 1999), and anxiety disorders (Cochran & Mays, 2000b;Sandfort et al, 2001) in homosexually active men when compared with heterosexually active men. Similarly, some, but not all, studies found higher rates of major depression (Gilman et al, 2001;Sandfort et al, 2001), suicide attempts (Gilman et al, 2001), some anxiety disorders (Gilman et al, 2001), and alcohol-and drug dependency disorders (Cochran & Mays, 2000b) in homosexually active women when compared with heterosexually active women.Because sexual orientation is a broader construct than same-gender sexual activity (Sell, 1997), the use of sexual behavior alone to determine identity has led to some concern about mis-classification bias in these studies (Bailey, 1999;Cochran et al, 2000;Cochran & Mays, 2000b), Indeed, Bailey (1999 suggested that this approach indexes not only sexual orientation but also, to some degree, impulsivity among those who are heterosexual but may engage in same-gender sexual behavior at times. The effect of this might be to overestimate rates of mental health morbidity.…”
mentioning
confidence: 99%
“…Several studies in large probability samples have shown that homosexuality is a risk factor for mental health problems (Cochran, Keenan, Schober, & Mays, 2000;Cochran, Sullivan, & Mays, 2003;Fergusson, Horwood, & Beautrais, 1999;Gilman et al, 2001;Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002;King et al, 2003;McDaniel, Purcell, & D'Augelli, 2001;Meyer, 2003;Sandfort, de Graaf, & Bijl, 2003;Sandfort, de Graaf, Bijl, & Schnabel, 2001;Skegg, Nada-Raja, Dickson, Paul, & Williams, 2003). Sandfort et al (2001), for instance, found in a large population sample of 7,076 heterosexually and homosexually active adults (aged 18-64 years) that homosexual men had a higher 12-month prevalence of mood disorders and anxiety disorders than did heterosexual men, while homosexual women had a higher 12-month prevalence of substance use disorders than did heterosexual women.…”
Section: Introductionmentioning
confidence: 99%